Active labour market policies: What works for the long-term unemployed? - Rainer Eppel; Ulrike Huemer; Helmut Mahringer; Lukas Schmoigl (Austrian Institute of Economic Research (WIFO), 2024)
There is still a lack of knowledge on how to effectively help the long-term unemployed into employment. We evaluate a wide range of active labour market policies for this target group, using a dynamic matching approach. Measures vary considerably in the extent to which they improve labour market prospects. Human capital-intensive training programmes that substantially enhance vocational skills and employment programmes are most effective, short activating job search training the least. Our results suggest that not only wage subsidies in the private sector, but also direct job creation in the public and non-profit sector can work, if properly designed.
Keywords: J24; J64; J68; 330; Long-term unemployment; Active Labour Market Policy; Public Employment Service; Training; Wage subsidies; Direct job creation